Prevalence and factors associated with road traffic crashes among truck drivers in Southeast Iran - Raheleh Hashemi Habybabady; Hassan Okati-Aliabad; Mohammad Sabouri; Mahdi Mohammadi; Alireza Ansari-Moghaddam (PLoS ONE, 2025)
Road traffic injuries are the second leading cause of death in Iran. The study investigated the prevalence and the influencing factors of Road traffic crashes (RTCs) among truck drivers in southeast Iran. In this cross-sectional study, 592 truck drivers were recruited using a multi-stage sampling method from November 2022 to February 2023. Data was collected through a researcher-administered questionnaire that included the crashes, individual characteristics, driving characteristics, work patterns, sleep and fatigue-related factors, workload, driving styles, and personality traits. Simple and multiple logistic regressions were used to assess the association between risk factors and crash involvement in the 3 last years. The surveyed drivers had a mean age of 37.4 ± 8.9 years, with an average driving history of 13.7 ±  7.6 years. Among the respondents, 28.4% reported involvement in crashes over the last 3 years, with 12.1% reporting one, 10% reporting two, and 6.3% experiencing three or more crashes. A significant portion of the crashes (42.5%) occurred between midnight and 6:00 a.m. In their lifetime, 24.2% of participants reported at least one sleep-related crash, 40.5% reported at least one fatigue-related crash, and 6.9% reported at least one crash resulting in a fatality. The odds of RTCs were higher among truck drivers who used drugs (OR = 2.03, 95% CI, 1.36-3.04), used mobile devices for texting (OR = 2.88, 95% CI, 1.56-5.30), neglected seat belt usage (OR = 1.81, 95% CI, 1.10-2.99), had accumulated traffic fines in the last year (OR =  8.18, 95% CI, 3.82–17.52, OR =  11.39, 95% CI, 5.42–23.92, OR =  17.78, 95% CI, 7.50–42.17, for 1-2, 3-6, and > 6 traffic fines, respectively), consumed sleeping pills (OR = 2.52, 95% CI, 1.19-5.35), engaged sleep driving (OR = 11.30, 95% CI, 7.18-17.80), extended their driving hours without a break (OR =  3.02, 95% CI, 1.55–5.87, for consecutive driving hours before taking a break ≥ 8), experienced fatigue while driving (OR =  1.98, 95% CI, 1.24–3.17, for sometimes experienced fatigue while driving), faced high visual demands (OR = 1.23, 95% CI, 1.02-1.50), exhibited a careless driving style (OR = 0.95, 95% CI, 0.91- 0.99), and had higher levels of neuroticism (OR = 1.05, 95% CI, 1.01-1.10). The study sheds light on the significant prevalence of road traffic crashes among truck drivers. The findings underscore a constellation of factors amplifying crash risks within this occupational group. These outcomes emphasize the multifaceted nature of road safety issues within the trucking industry, indicating the need for targeted interventions and preventive measures to enhance driver safety and reduce the incidence of road traffic crashes among truck drivers.